PENGARUH MODEL PROJECT BASED LEARNING DENGAN TUGAS CREATIVE MIND MAP TERHADAP KEMAMPUAN KONEKSI MATEMATIKA DAN HASIL BELAJAR SISWA - Raitu, Hisyam; Kurniawan, Ade (Media Pendidikan Matematika, 2018)
The purpose of this research was determining the effect of Project Based Learning model( PjBL) with the task of Creative Mind Map toward student mathematics connecting ability and learning outcomes at VIIth grade students ofÂ MTs Negeri Anaraja on subject matter Triangle. The kind of this research is experimental research. The desain of this research is Nonequivalent Control Group Design. The population in this research was the VIIth grade students of MTs Negeri Anaraja in academic year 2015/2016. The Sampling technique was the Non-probability Sampling technique that is the Purposive Sampling. So the sample chosen is class VII-2 as the control sample class with discovery learning model and class VII-3 as the experiment sample with PjBL model with the task of creative mind map. The data of student mathematical connection ability were taken by Observation Mathematical Connections Ability Sheet, and students learning outcomes data were analyzed using t-test. Based on the data analysis, it was known that the average percentage of students’ mathematical connection ability experimental class was 37% with an average value of 23.785 and the control class was 33.33% with an average value of 23.38421, this suggests was showed that the mathematics connecttion ability of students still low. While the results of t-test analysis showed that there was no significant difference between experimental class learning outcomes with control class learning outcomes. It can be seen from the price Â of ttest was smaller than the ttable , with dk = 37 at the level of error was 5%. So it can be concluded that there is no effect of the PjBL model with the task of Creative Mind Map toward student mathematics connection ability and student learning outcomes at Â the VIIth grade students of MTs Negeri Anaraja in academic year 2015/2016.